Synthesis, Characterization, and Antioxidant Activity of Cr(III), Mn(II), Fe(III), Co(II) and Ni(II) Complexes with Mixed Azo Dye and Bipyridyl Ligands - Al-Dabbagh, Areej Kamal; Mawlood, Mawlood Khalid; Al-Hamdani, Abbas Ali Salih (Indonesian Journal of Chemistry, 2025)
Mixed ligands reaction of [2-[(3-hydroxyphenyl)diazinyl]-1,2-benzothiazol-3(2H)-one-1,1-dioxide] (H2L, primary ligand) and bipyridyl (secondary ligand) with salts of Cr(III), Mn(II), Fe(III), Co(II) and Ni(II) was performed. A series of air-stable complexes with distinctive octahedral moieties was created by equal molar ratio (1:1:1). The formation of these compounds was verified using detecting analysis techniques incorporating mass spectra, which validated the achieved geometries. Fourier transform infrared (FTIR) analysis demonstrated how the ligands (H2L and bipyridyl) are chelated as tridentate (ONO) and bidentate (NN) groups, respectively and the coordination with the metal ions. Thermal decomposition studies using pyrolysis (TGA and DSC) verified that water residues could be coordinated with metal complexes. Additionally, elemental micro-analysis, chlorine amount test, molar conductivity and melting points examination were carried out. Magnetic sensitivity of the susceptibility and ultraviolet-visible (UV-vis) spectrophotometry can also reveal the coordination existence with the metals and complexes formation. The compounds' antioxidant records were finally evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical as a free radical method. It was compared to that of gallic acid as an accordingly standard antioxidant substance with its IC50 value. These complexes could restrict free radicals; [Fe(L)(bipy)Cl] has the best antioxidant activity, whereas [Ni(L)(bipy)H2O] has the lowest.